Distant mothering, grandparenting, intergenerational coparenting relationship, and child adjustment: evidence from Chinese families with young left-behind children - Liang, Ruwen; Van Leeuwen, Karla (Frontiers in Psychology, 2025)
IntroductionIn China, it is a common practice for rural-to-urban migrant parents, due to working conditions, to leave their children with grandparents in their rural hometowns, and to raise their child from a distance (e.g., via mobile phone). Little is known about the association between (co-)parenting processes and child adjustment in these families. This cross-sectional study examined, in households with left-behind children (LBC), how positive grandparenting and distant mothering are associated with the child’s adjustment in home and preschool settings. The quality of the mother-grandparent coparenting relationship was hypothesized to be a moderator in this association.MethodsQuestionnaire data were collected from 185 triads, namely preschool teachers (reporting child adjustment), grandparents (reporting child adjustment, grandparenting, and coparenting relationship quality), and migrant mothers (reporting coparenting relationship quality and distant mothering) of LBC aged 3 to 6.ResultsMultiple hierarchical regression analyses showed that more positive grandparenting was associated with more child prosocial behavior and fewer difficulties. A significant interaction effect indicated that low coparenting relationship quality can be a risk factor: when mothers reported low levels of distant proactive control and the quality of the coparenting relationship was low, children showed less prosocial behavior.DiscussionA comprehensive family intervention program involving parents and grandparents at the same time may be a better option given the interrelatedness of (behaviors of) members within different family subsystems.